Vírus Linfotrópico de Células T humano HTLV) – Tipo 1 e Tipo 2: estudo epidemiológico dos doadores de sangue soropositivos – Maranhão, Brasil - CRUZ, Dinaura Maramaldo (2011)
The type 1 and type 2 virus human T-lymphotropic type 1 are human retroviruses, that destroy or transform lymphocytes causing diseases that are externalized years or even decades after primary infection. The virus has a worldwide prevalence varies by geographic region and population, Brazil is assigned the highest absolute number of carriers. Risk factors such as transfusions, sharing needles, sexual contact and breastfeeding are no ways to prevent transmission. The objective of this study was the epidemiological profile of the sociodemographic and blood donors, the Blood Center of Maranhão - HEMOMAR with positive serology for HTLV-1/2, identifying the virus types. We analyzed the records of 924 blood donors of the Blood Center of Maranhão - HEMOMAR, which showed positive pattern and indeterminate ELISA test (OD / CO > 0.800) and the Western blot test in the period January 2002 to December 2009. Reactivity was identified for HTLV-1 / 2 by ELISA in the general population of donors is 0.24% (n = 924/398.362) and 0.02% in the Western blot test. Sex, age and color were statistically significant. Considering the group studied, there was a significant number of females, average age 40 years predominantly brown and black. Most had less than eight years. Among the cases 35.6% had co-infection with other serological markers, with higher prevalence for hepatitis B, and Hepatitis C, syphilis and HIV. The Western Blot test revealed the circulation of HTLV type 2 (2,4%) between subjects, but with higher prevalence for HTLV type 1 (70,1%). The presence of HTLV-1/2, the situation of co-infections associated with HTLV indicate the need for adoption of effective public health measures focused on the implementation of prevention strategies, since even in the presence of population studies suggests the existence of risk factors for transmission. Epidemiological studies have been relevant to advances in scientific knowledge about HTLV. The availability of qualified information on the means of transmission, prevention and risk perception, considering cultural and social aspects, are mechanisms for intervention in controlling the virus.